CircPCMTD1 Acts as the Sponge of miR-224-5p to Promote Glioma Progression - Zheng, Si-Qi; Qi, Yue; Wu, Jun; Zhou, Fen-Li; Yu, Hao; Li, Lu; Yu, Bo; Chen, Xiao-Fan; Zhang, Wei (Frontiers in Oncology, 2019)
Glioma is the most common malignant tumor of the central nervous system with high morbidity and mortality. Circular RNAs (circRNAs) are abundant non-coding RNAs, which contribute to tumor progression by competing with other endogenous RNAs such as microRNA (miRNA). MiRNA are a class of small noncoding RNAs which interrupt the translation of target mRNAs. CircPCMTD1 (hsa-circ-0001801) is a newly discovered circRNA that was found to be significantly upregulated in glioma. However, its function is unclear. In this study, circPCMTD1 upregulation promoted the cell viability, migration and invasion dramatically, while the inhibition of circPCMTD1 led to significant reduction of tumor growth in vivo. MiRNAs microarray analyses on circPCMTD1 silencing models in U251 and U118MG cells were performed and the results suggested that circPCMTD1 knockdown could upregulate the expression of miR-224-5p and downregulate the expression of mTOR, one of miR-224-5p target, in both cell lines. According to the prediction from circular RNA interactome and Targetscan, there was a complementary sequence in circPCMTD1 for miR-224-5p. Dual-luciferase reporter assay demonstrated that circPCMTD1 were targets of miR-224-5p. RIP assay was also performed to further confirm their directly interaction. Overexpression of miR-224-5p inhibited the viability and proliferation, migration, and invasion of U251 and U118MG glioma cells. In conclusion, circPCMTD1 could contribute to the promotion of glioma progression, and it may serve as the sponge of miR-224-5p to exert its function.